Molecular detection of Virulence Factors genes Associated with Immune Resistance in Klebsiella pneumonia (Medico Legal Update, 2020)
The current study was aimed to genotypically detection of genes encode outer membrane proteins relatedwith human serum resistance. A total of 33 isolates were identified as Klebsiella pneumonia according to themanual cultural characteristics and biochemical tests and then confirmed by Vitek -2 system. The numberof isolates according to site of infection were 14 (42.4%) isolates from wound infection, 15(45.4%) isolatesfrom urine, 1(3.03%) isolates from blood, 1(3.03%) isolates from vagina,1(3.03%) from ear swab and finally1(3.03%) isolates from stool. The present study demonstrated a positive relationship between the abilityof bacterial isolates to antibiotics resistance and the occurrence of some virulence genes. The moleculardetection of some virulence genes (htrA, rmpA, mrkA and iss) was done by conventional PCR technique.It was found that ,high occurrence of htrA gene was observed among Klebsiella pneumonia isolates whichwas found in 26(78% ) of isolates at 1071bp , then 17(51%) isolate were positive for rmpA gene at 967bp,whereas mrkA gene was recorded in 5(15.15%) isolates at 862 bp , and only 4(12.12%) isolates gavepositive result for iss gene at 450bp.